41 - THE EFFECTS OF FUNCTIONAL ELECTRICAL STIMULATION IN MARCH OF CHILDREN WITH HEMIPARETIC CEREBRAL PALSY (Fiep Bulletin - online, 2011)
The Cerebral Palsy (CP) acts in the implementation of the movements due to abnormal patterns of coordination, posture and muscle tone. The hemiparetic gait does not show the touch of the calcaneus at the beginning of the bipedal support because the previous tibial muscle does not produce enough strength to perform the movement of dorsiflexion. The stage of the push is also compromised as a result of the weakness of the surae triceps muscle, constituting limiting factor for gait. Morphological studies suggest that the weakness of the paretic muscle is more disabling than the spasticity. The Functional Electrical Stimulation (FES) promotes the strengthening with the possibility of reducing the cortical asymmetry, as it involves processes related to voluntary movement. This present work have as objective to compare the effects of FES in the functionality of gait in patients with CP after its implementation in the previous tibial and triceps surae muscles. The results obtained by the GMFM score showed greater progress in the patient who received the FES in the surae triceps muscle, as well as improvement of the passive ADM and increase of muscular strength in dorsiflexors and plantiflexors, reducing the degree of spasticity and changes in the variables of the gait. The FES showed positive results in treating spastic muscles with developments in the functionality of the gait.
Keywords: Cerebral Palsy; Functional Electrical Stimulation